Examining the neurodevelopmental and motor phenotypes of Bohring-Opitz syndrome (ASXL1) and Bainbridge-Ropers syndrome (ASXL3) - Ayoub, Maya C.; Anderson, Jeffrey T.; Russell, Bianca E.; Wilson, Rujuta B. (Frontiers in Neuroscience, 2023)
Background: Chromatin Modifying Disorders (CMD) have emerged as one of the most rapidly expanding genetic disorders associated with autism spectrum disorders (ASD). Motor impairments are also prevalent in CMD and may play a role in the neurodevelopmental phenotype. Evidence indicates that neurodevelopmental outcomes in CMD may be treatable postnatally; thus deep phenotyping of these conditions can improve clinical screening while improving the development of treatment targets for pharmacology and for clinical trials. Here, we present developmental phenotyping data on individuals with Bohring-Optiz Syndrome (BOS -ASXL1) and Bainbridge-Ropers Syndrome (BRS -ASXL3) related disorders, two CMDs highly penetrant for motor and developmental delays.Objectives: To phenotype the motor and neurodevelopmental profile of individuals with ASXL1 and ASXL3 related disorders (BOS and BRS). To provide a preliminary report on the association of motor impairments and ASD.Methods: Neurodevelopmental and motor phenotyping was conducted on eight individuals with pathogenic ASXL1 variants and seven individuals with pathogenic ASXL3 variants, including medical and developmental background intake, movement and development questionnaires, neurological examination, and quantitative gait analysis.2 This is a provisional file, not the final typeset article Results: Average age of first developmental concerns was 4 months for individuals with BOS and 9 months in BRS. 100% of individuals who underwent the development questionnaire met a diagnosis of developmental coordination disorder. 71% of children with BOS and 0% of children with BRS noted movement difficulty greatly affected classroom learning. Participants with BRS and presumed diagnoses of ASD were reported to have more severe motor impairments in recreational activities compared to those without ASD. This was not the case for the individuals with BOS.Conclusions: Motor impairments are prevalent and pervasive across the ASXL disorders with and without ASD, and these impairments negatively impact engagement in school-based activities. Unique neurodevelopmental and motor findings in our data include a mixed presentation of hypo and hypertonia in individuals with BOS across a lifespan. Individuals with BRS exhibited hypotonia and greater variability in motor skills. This deep phenotyping can aid in appropriate clinical diagnosis, referral to interventions, and serve as meaningful treatment targets in clinical trials.